In Context: Reading Skills for Intermediate Students of English as A Second Language (USA Holt, Rinehart and Watson, 1982)
Immerse your students in refreshing and lively topics while increasing their vocabulary base and preparing them for academic assignments. This series for beginning to high-intermediate learners offers robust comprehension activities that encourage students to access and interact with text and to develop reading and critical thinking skills
Preliminary Unit: Learning skills for reading. 1. Communication --- 2. Nature recycles water --- 3. The cost of education --- 4. Travel and adventure --- 5. A country on the move --- 6. Why people buy --- 7. Energy and building design --- 8. Against the storm --- 9. "Ever tried talking to a computer?" --- 10. Using the mind against disease
Jean Zukowski/Faust [and others]
Keywords: Languages (3GddZGJs; General -- Textbooks for foreign speakers; English language; Reading comprehension; Readers; Vocabulary; Language acquisition -- Research